The Definition of Translation in Davidson’s Philosophy: Semantic Equivalence versus Functional Equivalence - Ervas, Francesca (TTR)

(untitled) (Association canadienne de traductologie, 2012)
This article discusses how, in addition to providing a definition for translation, the concept of equivalence may explain why we can say that sentence S in language L is a translation of sentence S1 in language L1. It analyzes two main kinds of equivalence that are used in analytical philosophy to define translation: semantic equivalence and functional equivalence. This analysis shows that drawing a distinction between semantic and functional equivalence is a way to understand the distinction between different levels or aspects of meaning. Both semantic equivalence, introduced by Gottlob Frege, and functional equivalence, proposed by Wilfrid Sellars, were developed in Donald Davidson’s theory of meaning. After discussing the limits of Davidson’s definitions of equivalence, this article will argue that functional equivalence is a reason for comparing Davidson’s philosophy to positions such as those expressed by Hans-Georg Gadamer’s hermeneutics.